KEBOLEHULANGAN (REPRODUCIBILITY) DALAM PEMBUATAN SEL SUPERKAPASITOR DARI KAYU KARET - Rizki, Afdhal; Taer, Erman; ', Rika (Jurnal Online Mahasiswa (JOM) Bidang Matematika dan Ilmu Pengetahuan Alam, 2015)
A research has been conducted on reproducibility measurement of specific capacitance of supercapacitor cell. The purpose of this study was to measure reproducibility capacitive properties of supercapacitor cell based on rubber wood electrode. Synthesis of supercapacitor cell was started by producing electrode with carbonization process in vacuum flowing N2 gas at a temperature of 7000 C and through physical activation using CO2 gas with a temperature of 900° C for 2 hours. Specific capacitance of the cell was measured using cyclic voltammogram at scan rate of 1 mV/s – 100 mV/s for three different cells. The highest specific capacitance of 78.692 F/g with 3.274 % error percentage to be found at 1 mV/s of scan rate while the highest error percentage was observed at 16.785 % for 100 mV/s. Scanning Electron Microscope micrograph from the top and side view with magnification of 500 and 3000 X showed a pore in the form of a tunnel straight down on the samples. X-Ray Difraction measurement showed the peaks of carbon electrode occurred at 2θ of 24,442o - 44.101 o due to the presence of carbon with their crystal orientation of (002) and (100). The overall results showed the measurement of specific capacitance of supercapacitor cell was found to be accepted with low standard deviation (< 5 %) especially for measurement of 1 – 50 mV/s in scan rate.